Three‐dimensional anisotropic moisture absorption in quartz‐reinforced bismaleimide laminates. Issue 1 (26th March 2013) - Grace, L.R.; Altan, M.C.
<x xml:space="preserve">Abstract</x> The three‐dimensional anisotropic moisture absorption behavior of quartz‐fiber‐reinforced bismaleimide (BMI) laminates is investigated by collecting 21 months of experimental gravimetric data. Laminates of six, twelve, and forty plies and various planar aspect ratios are used to determine the three‐dimensional anisotropic diffusion behavior when exposed to full immersion in distilled water at 25°C. The long‐term moisture absorption behavior deviates from the widely used Fickian model, but can be accurately captured by the three‐dimensional, anisotropic hindered diffusion model (3D HDM). Excellent agreement is achieved between experimental gravimetric data and the 3D HDM for all laminate thicknesses. Recovered model parameters are shown to slightly vary with laminate thickness due to the small changes in the cured‐ply thickness. However, model parameters identified for a given laminate thickness are observed to accurately predict the absorption behavior of samples with different planar dimensions. Equilibrium moisture content of 1.72, 1.69, and 1.84% and corresponding diffusion hindrance coefficients of 0.807, 0.844, and 0.671 are recovered for six, twelve, and forty‐ply laminates, respectively, thus confirming strong non‐Fickian behavior. Moisture absorption parameters may be determined successfully at 16.5 months of immersion, before reaching approximately 85% of the equilibrium moisture content at 21 months. Subsequent gravimetric measurements up to 21 months are consistent with the predicted long‐term behavior. POLYM. ENG. SCI., 54:137–146, 2014. © 2013 Society of Plastics Engineers